PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS MEDIA GARIS TANGGA TERHADAP KETERAMPILAN BERHITUNG PERKALIAN SISWA KELAS 2 SDN 10 TIGA DESA - Domi Acila; Totok Victor Didik Saputro (STKIP Subang, 2026)
The Problem Based Learning (PBL) learning model is an instructional strategy that requires students to work collaboratively in finding solutions to contextual problems. This study aims to determine the effect of the implementation of the PBL model based on ladder media on the basic multiplication calculation skills of 2nd grade students of SDN 10 Tiga Desa. The type of research used is quantitative with a Pre-Experimental design in the form of One-Group Pretest-Posttest Design. The study population included all 2nd grade students of SDN 10 Tiga Desa with a saturated sample of 18 students who met the criteria. The data collection technique used a test instrument in the form of an essay of 10 questions and an observation sheet for learning activities. Data were analyzed descriptively and inferentially using reflection tests (normality, homogeneity, linearity) as well as simple linear regression tests and t-tests (Paired Sample T-Test). The results showed a significant increase in the average value (mean) from 56.11 at the pretest to 80.00 at the posttest. The simple linear regression test produced an R Square value of 0.7361, which indicates that the ladder-based PBL model contributed 73.61% to students' multiplication arithmetic skills. Furthermore, the t-test produced a tcount value of -5.006 which was significantly greater than ttable (2.119) with a probability value of 9.72 x 10-5 < 0.05. Thus, H0 was rejected and Ha was accepted. It can be concluded that the implementation of the ladder-based PBL model had a significant positive effect in boosting the numeracy skills of lower-grade students.